Implementation of Management Functions at PT Pegadaian (Persero) - Finthariasari, Meilaty; Pitra, Ahmad; Mukadar, Amir; Humairah, Mifta; Fauziah, Fenty (Journal of Social Work and Science Education, 2024)
This research aims to investigate and analyze the implementation of management functions at PT. Pegadaian (Persero) Lebong Regency. Considering the many functions of management, this research will only discuss four management functions, namely, planning, organizing, supervising, and directing. This research uses descriptive and qualitative research methods. In the data collection process in this research, researchers used observation, interview, and documentation techniques. In analyzing the data, researchers used data analysis techniques with data reduction steps, data presentation, and drawing conclusions. The research results show that employees already have their respective duties and obligations in dividing tasks as well as arranging activities by planning in advance. Apart from planning the division of tasks according to the abilities of each employee, PT. Pegadaian (Persero) Lebong Regency also provides good guidance to employees. By carrying out training activities that all employees must participate in. Then, in terms of supervision of PT Pegadaian (Persero), Lebong Regency also did well. Supervision is very important in a company so that the evaluation process runs smoothly.